Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1994
DOI: 10.1115/94-gt-496
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Flame Stability in a Research Dump Combustor

Abstract: The lean blowout process is studied in a simplified, nominally diffusion flame research combustor that incorporates the essential features of the combustor primary zone for an aircraft gas turbine engine. The research combustor is provided with extensive optical access. To investigate the blowout, a variety of diagnostic techniques are employed, including direct flame observation, laser-Doppler anemometry, spontaneous OH-imaging, thin-filament pyrometry, laser-induced fluorescence OH-imaging, coherent anti-Sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Computational fluid dynamics (CFD) analysis, coupled with findings by other researchers (Ref. 5,6) and empirical correlations were used to determine potential improvements to peak wall temperatures and LBO. These studies indicated that significant performance improvements could be achieved by modifying the combustor dome air feed configuration.…”
Section: Combustor Configurationmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) analysis, coupled with findings by other researchers (Ref. 5,6) and empirical correlations were used to determine potential improvements to peak wall temperatures and LBO. These studies indicated that significant performance improvements could be achieved by modifying the combustor dome air feed configuration.…”
Section: Combustor Configurationmentioning
confidence: 99%